2022
DOI: 10.1002/humu.24357
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the proportion of pathogenic variants from breast cancer case–control data: Application to calibration of ACMG/AMP variant classification criteria

Abstract: For genes with reliable estimates of disease risk associated with loss-of-function variants, case-control data can be used to estimate the proportion of variants of typical risk effect for defined groups of variants, of relevance for variant classification. A calculation was derived for a maximum likelihood estimate of the proportion of pathogenic variants of typical effect from case-control data and applied to rare variant counts for ATM, BARD1, BRCA1, BRCA2, CHEK2, PALB2, RAD51C, and RAD51D from published br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The Hereditary Breast Ovarian and Pancreatic Cancer VCEP has designated BP7 application for variants at or beyond positions +7/-40 in the ATM gene. The ENIGMA BRCA1 and BRCA2 VCEP specifications justify the application of BP7 for variants outside splice motifs based on maximum likelihood estimation analysis of breast cancer case-control data 57 with results indicating that location of an intronic variant at or beyond positions +7/-21 provides moderate evidence against pathogenicity - even without applying a bioinformatic prediction filter.…”
Section: Resultsmentioning
confidence: 99%
“…The Hereditary Breast Ovarian and Pancreatic Cancer VCEP has designated BP7 application for variants at or beyond positions +7/-40 in the ATM gene. The ENIGMA BRCA1 and BRCA2 VCEP specifications justify the application of BP7 for variants outside splice motifs based on maximum likelihood estimation analysis of breast cancer case-control data 57 with results indicating that location of an intronic variant at or beyond positions +7/-21 provides moderate evidence against pathogenicity - even without applying a bioinformatic prediction filter.…”
Section: Resultsmentioning
confidence: 99%
“…BP1 was used to capture strong evidence against pathogenicity for a variant outside of a known clinically important functional domain predicted to encode a silent or missense/in-frame substitution only (without known or predicted impact on splicing), with strength assigned from probability based studies 17 , and VCEP consideration of large-scale case-control findings for missense variants. 20 ; 21 PP4 and BP5 were repurposed to capture combined LR estimates towards pathogenicity (PP4) or against pathogenicity (BP5), as derived from calibrated multifactorial likelihood ratio analysis (but excluding any direct statistical measurement of bioinformatic prediction scores, to avoid overlap with other computational codes).…”
Section: Resultsmentioning
confidence: 99%
“…Large part of variations, in many genes the majority, are benign and without phenotype. Experimental studies [ 252 ] and predictions [ 209 , 210 , 253 ] have indicated that genes display a wide range of vulnerabilities for genetic alterations. Even in Cancer Gene Census -classified cancer-related genes [ 254 ] with substitutions, just 40% of amino acid substitutions were predicted to be harmful [ 255 ].…”
Section: Genetic Heterogeneity and Diseasesmentioning
confidence: 99%